Comparative study of elementary science books in Iran and Russia with Approach of attention to process skills - Sayedamin Azimi; Nasim Soleimani (پژوهش در نظام‌های آموزشی, 2021)
The main purpose of this study was a comparative study of the level of attention to process skills in the first to third grade science textbooks of Iran and Russia in 1399-1400. It is a descriptive research of content analysis. The statistical population of the study consists of all the books "Experimental Sciences" of Iran and "The World Around Us" in Russia in the first, second and third grades. The tool of book content analysis was a researcher-made checklist of process skills and the results were analyzed based on George Brady's model in four stages of description, interpretation, proximity and comparison. The results showed that in the Iranian elementary science textbooks, the components of comparison and classification, skill of using tools and communication skills are more emphasized. In Russian science textbooks, more attention has been paid to the components of observation, prediction, estimation, interpretation of findings and conclusions. The results also show that the components of discovering and establishing numerical relationships, hypothesizing, measuring skills and conducting research in both countries have received less attention. Analysis showed that the level of attention to process skills is low compared to the volume of book content in the elementary science textbooks of both countries. Thus, it is necessary to pay more attention to the components of process skills in compiling textbooks in the two countries. It is suggested that in Iran, lesson topics be related to daily life activities. Also, in Russia, the topic of conversation and communication should be considered.